Lichen planus : a case report - Puri, Rajiv (Journal of Case Reports in Dental Medicine, 2020)
Oral lichen planus (OLP) is an autoimmune, mucocutaneous disease involving  oral mucosa, skin, scalp, genital mucosa and nails. It is  the common skin diseases present in the oral cavity. An immune mediated reaction is recognized in lichen planus, but exact etiology is unknown. The disease mostly affects middle-aged females and is infrequently found in children. The atrophic and erosive forms of OLP are less common. Potential of OLP to malignancy is controversial. Although relatively, oral lichen planus is the target of controversy, mainly in relation to its pathogenesis and possible potential for malignancy.  Hence it is essential for the clinicians to keep an index of suspicion for all intraoral lichenoid lesions. Periodic follow-up of patients with OLP is recommended.